Inhaled Formoterol-Fluticasone Single Inhaler Therapy in Asthma: Real-World Efficacy, Budget Impact, and Potential to Improve Adherence - V. Rajesh; Jolsana Augustine; R. Divya; Melcy Cleetus (Canadian Respiratory Journal)
Asthma is the commonest chronic disease affecting airways in humans and has an increasing global disease burden. Inhaled corticosteroids (ICS) are the first-line therapeutic option for asthma, and addition of a long-acting beta 2-agonist (LABA) has been shown to improve asthma control. A combination of the two agents in a single inhaler is beneficial with regard to ease of administration and patient compliance. Various ICS-LABA formulations are available across various countries in the world, one among them being formoterol-fluticasone. Both formoterol and fluticasone have pharmacologic peculiarities which places the combination in a uniquely advantageous position when it comes to asthma therapy. The present review focuses on some of the, hitherto, less explored aspects of this combination inhaler such as real-world efficacy, impact on budget allocation, results of switch-over therapy, and potential to improve adherence to asthma treatment. It also provides practical recommendations on positioning it in real-world asthma management.